Sensitive assay for measuring tetracycline levels in gingival crevice fluid. - Gordon, J M (1980)
An increased interest in the clinical use of antibiotics as an adjunct to periodontal therapy has created a need to determine antibiotic concentrations in fluid obtained from the gingival crevice. For this purpose, an increase in sensitivity beyond that possible with current tetracycline assays is essential because sample volumes of gingival fluid typically obtained are less than 0.5 microliter. This report describes the development of an agar-diffusion assay technique capable of measuring the concentration of tetracycline in samples of gingival crevice fluid in the range of 0.1 to 4.0 microgram/ml. The assay will detect amounts of tetracycline in gingival crevice fluid samples as low as 50 pg. The high sensitivity of this assay was achieved by optimizing the medium depth, inoculum density, agar concentration, pH, period of prediffusion, and selection of basal medium. Use of this assay indicated that the concentration of tetracylcine in gingival crevice fluid was greater than that found in blood and persisted at elevated levels for longer periods.